Blaze and the Mountain Lion - Anderson, C. W.; Nang Chan Yeema (New York, USA Aladding Paperbacks, 1993)
While riding through the open country near his family's ranch house, Billy and his pony Blaze come across a dangerous mountain lion.
Keywords: Story Collection